Enhancing Banking Service Quality through Digital Transformation: A Strategic Analysis of a Regional Development Bank in Papua - Giyai, Simon; Maju Simatupang, Batara; Budhijana, R. Bambang; Pracoyo, Antyo (Dinasti Publisher, 2026)
Digital transformation has become a critical driver in enhancing banking service quality, particularly in regions characterized by infrastructural limitations and low digital literacy. This study aims to formulate strategic approaches to improving service quality through banking digitalization at a regional development bank in Papua, Indonesia. A qualitative case study approach was employed, utilizing semi-structured interviews and document analysis. Data were analyzed using SWOT and the Quantitative Strategic Planning Matrix (QSPM) to identify and prioritize strategic alternatives. The findings reveal that the most effective strategy is the development of inclusive and context-based mobile banking services, which enhance accessibility, operational efficiency, and customer satisfaction. The results demonstrate that successful digital transformation in geographically constrained regions depends not only on technological readiness but also on the organization’s ability to adapt to local socio-economic conditions and varying levels of digital literacy. This study contributes to the literature by extending the bank 4.0 concept into frontier regions through an adaptive and context-sensitive digital banking framework.